Two new tardigrade species from Romania (Eutardigrada: Milnesiidae, Macrobiotidae), with some remarks on secondary sex characters in Milnesium dornensis sp. nov. - Ciobanu, Daniel Adrian; Roszkowska, Milena; Kaczmarek, Łukasz (Zootaxa, 2015)
In two moss and lichen samples collected in Romania, two new eutardigrade species were found. Milnesium dornensis sp. nov. belongs to the granulatum group and differs from most of other species in this group mainly by having a different claw configuration ([3-3]-[3-3]) and by some morphometric characters. Minibiotus diversus sp. nov. is very similar to M. gumersindoi Guil & Guidetti, 2005 and M. weglarskae Michalczyk et al., 2005, but differs from these and other congeners by the cuticular pore arrangement and morphometric characters of both adults and eggs. Males and females of the newly described Milnesium species differ not only by the shape and structure of claws I, but also by other morphometric characters. Males of Milnesium dornensis sp. nov. are smaller, more slender, have shorter papillae and relatively longer claws on legs III–IV.